2019
DOI: 10.1021/acs.iecr.9b02887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Water Removal Method on Tetraethyl Orthosilicate Direct Synthesis: Experiment and Process Assessment

Abstract: A direct synthesis pathway of tetraethyl orthosilicate from silica and ethanol was recently proposed. Although this pathway has many advantages over the conventional one producing tetraethoxysilane (TEOS) from metallurgical silicon, its potential can be further increased by the effective removal of its byproducts. This study investigates the removal of the water byproduct, which reduces the TEOS product yield and enhances the loss of raw materials. Several inorganic dehydrating agents were examined under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Recently, our group has developed a direct synthesis of TROS from SiO 2 and alcohols. This method appears promising because of its nontoxicity and the use of abundant alcohols. However, SiO 2 is thermodynamically stable, and the H 2 O byproduct easily reacts with the TROS product to form oligomeric or polymeric SiO 2 .…”
Section: Synthesis Of Tros From Sio2mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group has developed a direct synthesis of TROS from SiO 2 and alcohols. This method appears promising because of its nontoxicity and the use of abundant alcohols. However, SiO 2 is thermodynamically stable, and the H 2 O byproduct easily reacts with the TROS product to form oligomeric or polymeric SiO 2 .…”
Section: Synthesis Of Tros From Sio2mentioning
confidence: 99%
“…In the direct synthesis of TEOS via the reaction between SiO 2 and ethanol, the removal of water using dehydrating agents strongly influences the yields and economic and environmental implications . CaO was found to be the most effective dehydrating agent among various candidates, such as MS, CaCl 2 , MgSO 4 , and Na 2 SO 4 , which produced a TEOS yield of 76%.…”
Section: Synthesis Of Tros From Sio2mentioning
confidence: 99%
“…[12] Key to shifting the equilibrium reaction in Eq. ( 9) is the presence in an upper autoclave of the molecular sieves promoting the reaction between silica and ethanol by adsorbing water molecules vaporized from the reaction mixture (without dehydrating agent, the TEOS yield is only 4 %), [26] minimizing formation of hexaethoxydisiloxane (Eq. ( 10)):…”
Section: Production Of Biobased Silicamentioning
confidence: 99%
“…Research continued, and the Japan-based team eventually reported that the use of cheap and readily available CaO as dehydrating agent further enhances the economic viability of the process. [26] Together, the biobased routes to high-purity Si, SiO 2 and Si(OR) 4 entirely by-pass the need for Si MG derived by the carbothermal reduction of quartz, establishing a circular bioeconomic route to all the primary silicon compounds employed in the chemical industry. Indeed, also chloromethane, a key raw material for the silicone industry, reacted with elemental silicon in the Rochow-Müller "direct process" to form methylchlorosilanes, can be readily synthesized from alkoxysilanes TEOS or TMOS.…”
Section: Production Of Biobased Silicamentioning
confidence: 99%
“…For example, R. Laine et al [17] used SiO 2 as starting material to react with excess ethylene glycol under the catalysis of a strong base to produce spirosilane firstly, which was then subjected to alcohol exchange to get TEOS. Similarly, N. Fukay et al [18,19] used strong bases and a significant amount of dehydrating agent to promote the reaction of SiO 2 with ethanol to get TEOS. These studies have greatly enriched and advanced the methods for the preparation of alkoxysilanes.…”
Section: Introductionmentioning
confidence: 99%